Towards addressing African cultural and Christian religion’s intolerance towards female teacher and the girl child for effective teaching, learning and peace in Zimbabwe Primary Schools: A case study of Gweru District. - Saiden, Thondhlana (Advances in Social Sciences Research Journal, 2017)
The study aimed at unravelling the effect of culture and religion on the learning of the girl child and the teaching of female teachers. It also aimed at how culture and religion led to peace in primary schools. The study was qualitative and was a case study of Gweru District primary schools. The study sample was 100 female teachers and 60 girl children who were purposively sampled. The study was guided by ethnography. The instruments used were quester-views, focus group discussion schedules and interview schedules. Among the findings of the study were such issues as: African women culturally, are subservient to men, Christian religion requires women to take their husbands as masters, African females are not allowed to air their views at gatherings, African females are prone to gossip, African males are allowed to marry as many wives as they wish so there is no crime in having extra marital affairs yet women are not allowed and the issue of division of labour in the home between male and female children is leading to female children having a dislike of male tasks. Much of the findings on the girl child agree with what the female teachers had aired except the issue of bullying. The two groups recommended such strategies as: counselling sessions, training in intercultural appreciation, multicultural education, interfaith education and anti-bullying campaigns and education among other recommendations.